Fabrication of Cu–Zn–Sn–S–O Thin Films by the Electrochemical Deposition Method and Application to Heterojunction Cells - Kai Yang; Masaya Ichimura (International Journal of Photoenergy, 2012)
A new multinary semiconductor Cu2ZnSnS4−𝑥O𝑥 (CZTSO), which does not contain toxic elements and expensive rare metals, was fabricated by the electrochemical deposition (ECD) method. CZTSO thin films were deposited onto indium tin oxide (ITO-) coated glass substrates by DC and two-step pulsed ECD from aqueous solutions containing CuSO4, ZnSO4, SnSO4, and Na2S2O3. The films deposited by pulsed ECD contained smaller amount of oxygen than those deposited by DC ECD. The films had band gap energies in a range from 1.5 eV and 2.1 eV. By a photoelectrochemical measurement, it was confirmed that CZTSO films showed p-type conduction and photosensitivity. CZTSO/ZnO heterojunctions exhibited rectification properties in a current-voltage measurement.